1997
DOI: 10.1074/jbc.272.10.6812
|View full text |Cite
|
Sign up to set email alerts
|

Low Density Lipoprotein Receptor-related Protein Modulates the Expression of Tissue-type Plasminogen Activator in Human Colon Fibroblasts

Abstract: Human colon fibroblasts (HCF) produce tissue-type plasminogen activator (t-PA) in culture, but after 24 -48 h, t-PA ceases to accumulate in the medium. Here, we report negative feedback regulation of t-PA expression, exerted by t-PA or complexes of t-PA with its physiological inhibitor, plasminogen activator inhibitor type 1 (PAI-1). Inhibition of t-PA expression could be induced by addition of exogenous t-PA or t-PA⅐PAI-1 complexes and reversed by monoclonal antibody directed against the active site of t-PA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…For example, our recent data suggest that negative feedback regulation of tissue plasminogen activator expression in colon fibroblasts is mediated via cell surface LRP (63). These observations suggest that at least one LRP ligand may modulate its own synthesis through communication between LRP and the transcriptional machinery of the cell.…”
Section: Discussionmentioning
confidence: 98%
“…For example, our recent data suggest that negative feedback regulation of tissue plasminogen activator expression in colon fibroblasts is mediated via cell surface LRP (63). These observations suggest that at least one LRP ligand may modulate its own synthesis through communication between LRP and the transcriptional machinery of the cell.…”
Section: Discussionmentioning
confidence: 98%
“…First, several studies have shown that apoE3, a ligand of LRP, increases neurite extension via LRP (Bellosta et al, 1995;Holtzman et al, 1995;Narita et al, 1997). Second, our previous studies have shown that negative feedback regulation of tPA gene expression in colon fibroblasts is mediated via tPA interaction with cell surface LRP (Hardy et al, 1997). Third, recent studies have shown that the LRP tail interacts with a heterotrimeric GTP-binding protein (Goretzki and Mueller, 1998) and two cytoplasmic adaptor proteins, FE65 and mammalian Disabled (Trommsdorff et al, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…First, several studies have shown that apoE3, a ligand of LRP, increases neurite extension via LRP (1,11,23,37). Second, our previous studies have shown that negative feedback regulation of tissue plasminogen activator gene expression in colon fibroblasts is mediated via cell surface LRP (18). Third, studies have shown that the LRP tail interacts with a GTP-binding protein induces cAMP-dependent protein kinase activity (16).…”
Section: Discussionmentioning
confidence: 99%